*La visualidad producida en la palabra y los factores que dan relevancia y protagonismo en la construcción de texto en Pedro Nava - Pugas Panichi, Edina Rwegina; Contani, Miguel Luis (Íkala, Revista de Lenguaje y Cultura, 2007)
This article explains how, in the text construction by Brazilian memoirs writer Pedro Nava, words and expressions contribute to upgrading writing due to the level of visual background they produce. The method for analysis was derived from the concept of informativity as stated by Beaugrande and Dressler, and from the semiotic concept of icon. Results show that there is a correlation between informativity coming from associations through similarity and a visual relationship within the universe of the word, which infl uences the way the text is constructed and fi rmly improves in meaning and aesthetic. Received: 10-04-07 / Accepted: 23-05-07 How to reference this article: Pugas Panichi, E. R. & Contani, M. L. (2007). A visualidade produzida na palavra e os fatores que conferem relevância e destaque na construção do texto em Pedro Nava. Íkala. 12(1), pp. 145 – 161.